Synthesis of the novel MOF hcp UiO-66 employing ionic liquids as a linker precursor. Issue 41 (1st October 2018) - Ermer, Matthias; Mehler, Julian; Kriesten, Martin; Avadhut, Yamini S.; Schulz, Peter S.; Hartmann, Martin
Abstract : The novel MOFhcp UiO-66 is synthesized using the ionic liquid ([PBuMEE]2 [BDC]) as a linker precursor. Abstract : By using a terephthalate containing ionic liquid, a new metal–organic framework, hcp UiO-66, comprising (Zr12 O8 (OH)14 ) double clusters and terephthalate ligands has been synthesized. The hydrothermal synthesis ofhcp UiO-66 might help to establish metal–organic frameworks for industrial scale applications.